A strong correlation between glomerular filtration rate and filtration surface in diabetic nephropathy - Osterby, R; Parving, H H; Nyberg, G; Hommel, E; Jørgensen, H E; Løkkegaard, H; Svalander, C (Diabetologia, 1988)
Quantitative structural studies were performed in kidney biopsy specimens from 24 long-term Type 1 (insulin-dependent) diabetic patients with persistent albuminuria due to diabetic glomerulopathy. Ten patients were receiving antihypertensive treatment, and among the remaining patients the mean blood pressure was 142/91 mm Hg (SD = 11/9). The urinary albumin excretion rate showed a range from 100 to 5494 micrograms/min (geometric mean 688 micrograms/min.) Glomerular filtration rate also showed a wide range, from supranormal to markedly decreased values (128 to 28 ml.min-1. (1.73 m2)-1, mean 75). The filtration surface (interface between capillary and urinary space) per total number of nephrons (open + occluded) was estimated by combined light-and electron microscopy. The percentage occluded glomeruli as well as structural quantities in the open glomeruli were taken into account in this estimate. A highly significant correlation was seen between glomerular filtration rate and filtration surface per nephron (r = 0.77, p less than 10(-4). The percentage occluded glomeruli contributed significantly to the variation in glomerular filtration rate (for this relationship tested separately r = -0.78, p less than 10(-5). The volume of open glomeruli was even larger than that seen in early diabetic glomerular hypertrophy and tended to increase with the percentage of glomerular closure, indicating that a compensatory hypertrophy might have taken place. In the open glomeruli the filtration surface constituted a smaller percent of total capillary surface (the remaining part facing the mesangial regions) than in early diabetic patients and control subjects. Our study has demonstrated that reduced glomerular filtration surface is closely associated with reduced glomerular filtration rate in Type 1 diabetic patients with diabetic nephropathy.